Building capacity in primary care: the implementation of a novel 'Pharmacy First' scheme for the management of UTI, impetigo and COPD exacerbation. Issue 6 (24th January 2018) - Stewart, Fiona; Caldwell, Gail; Cassells, Kirstin; Burton, Jonathan; Watson, Anne
Abstract : Aim: This service aimed to improve patient access to treatment for urinary tract infections (UTI), impetigo and exacerbation of chronic obstructive pulmonary disease (COPD) and relieve pressure on general practice and out of hours services. Background: In 2016, a service (Pharmacy First) was introduced in Forth Valley for the management of UTI, impetigo and exacerbation of COPD using patient group directions in community pharmacies. Trained pharmacists supplied a limited range of prescription medicines. Pathways for GP referral were defined. After 5 months of implementation, the service was evaluated. Methods: A quantitative evaluation was undertaken. Feedback was sought from patients, GPs, pharmacists and GP reception staff, using structured questionnaires. Pharmacy records were used to assess referrals and pharmacy data summarised the number and type of consultations. Basic cost data was obtained from the Health Board. Findings: In all, 75 pharmacies (of 76), and all 55 GP practices in the area, participated in the service. Over a 5-month period, 1189 cases were managed, the majority being for UTI (75.4%) followed by impetigo (15.2%), then COPD (9.3%). Of all cases, 77.9% were prescribed medication by the pharmacist, 9.1% were given advice only and 16.7% were referred to the GP. Independent clinical assessment of a random sample of 30 GP referrals considered all to be 'appropriate'. Feedback was received from 69 pharmacists, 34 GPs, 54 reception staff and 73 patients. Patients were very satisfied with the service, most frequently citing the 'quick and efficient' access to treatment, and a 'professional service'. Two thirds of GPs (67%) and 59% of reception staff found the service useful, mainly because it reduced pressure on GP appointments. A further cost benefit evaluation would allow objective assessment of the value of this service.